Capacitive performance of binder-free carbon/carbon composite cryogels - Kraiwattanawong, Kriangsak; Sano, Noriaki; Tamon, Hajime (My University, 2013)
A carbon/carbon (C/C) composite cryogel was prepared by pouring a resorcinol-formaldehyde (RF) sol into vials containing cotton fibers, followed by solvent exchange with t-butanol, freeze drying and pyrolysis under inert atmosphere. The porous properties of C/C composites were analyzed by nitrogen adsorption, and their mesopore texture was observed by a scanning electron microscope. The capacitive performance of C/C composites was also analyzed by galvanostatic charge/discharge method and cyclic voltammetry. The results demonstrate that the capacitance can be increased with the increase of amount of cotton fibers added to C/C composites, because the broader micropore size distribution and the carbon tunnels of C/C composites promote the charge propagation inside the pore structure. The suitable pore texture and the carbon tunnels can play the crucial role relevant to the high surface area in order to obtain the high capacitance value. © 2012 Elsevier Inc. All rights reserved.
Keywords: Composite; Cotton fiber; Electric double layer; Pore structure; SEM